Equity principles: Using social theory for more effective social transformation in agricultural research for development - McGuire, Erin; Al-Zu’bi, Maha; Boa-Alvarado, Maria; Thi Thu Giang Luu; Sylvester, Janelle M.; Valencia Leñero, Eva Marina (Elsevier, 2024)
CONTEXT: Agricultural innovations and their applications are increasingly recognized as crucial mechanisms for achieving the 2030 Sustainable Development Goals (SDGs). Actors in agricultural research for development (AR4D) frequently use Agricultural Innovation Systems (AIS) frameworks to comprehend the ecosystems within which innovations are developed and scaled. Given the SDGs' emphasis on social outcomes, a reflection on social diversity, power, and the integration of social theory into AIS and AR4D tools is crucial for addressing the nuances of social objectives. OBJECTIVE: This research critically evaluates AIS frameworks and AR4D tools through applying social theory to enhance social outcomes. We offer practical application through the development of “Equity Principles for Social Transformation (EPs).” These EPs are designed to guide AR4D organizations in innovation and scaling efforts that effectively achieve meaningful social outcomes. Through this approach, we aim to enrich the conceptual understanding of equity within AIS and provide practical strategies for implementing these insights, thus empowering AR4D actors to be more effective. METHODS: We start by selecting key social theories to analyze global power imbalances and local social exclusion within AIS frameworks and AR4D tools. Using these theories, we examine three case studies to uncover gaps in their approach to social dimensions. We categorize these gaps through thematic analysis and formulate EPs informed by social theories and a practical understanding of AR4D tools. RESULTS AND CONCLUSIONS: Equity analysis of each case study reveals gaps in understanding social implications within upstream and downstream research efforts. These gaps include insufficient addressing of power dynamics and agency recognition, lack of comprehensive guidance on critical social components, oversight of cultural and institutional norms, exacerbation of social inequities, and the case studies' limitations in flexibility for addressing social inclusion effectively. Additionally, there is a notable lack of clear operational guidelines for applying the frameworks in diverse contexts, including the challenge of translating conceptual levels into local action. Seven EPs were developed: recognize AR4D power dynamics; define goals, anti-goals, and for whom; build global “horizontal” partnerships; acknowledge social differences among innovation users and non-users; innovate and curate innovation appropriately; assess impact and reflect; and develop systems capacity. SIGNIFICANCE: The EPs connect innovation systems with positive social change. They help AR4D professionals consider and evaluate the impact of innovation. The EPs provide an additional framework that enables AR4D practitioners to prioritize user needs from the beginning, challenge biases, and more effectively achieve the social objectives outlined in the SDGs.